Common chromosomal imbalances and stemness-related protein expression markers in endometriotic lesions from different anatomical sites: the potential role of stem cells - Silveira, Cassia G. T. [UNESP]; Abrao, Mauricio S.; Dias, Joao A.; Coudry, Renata A.; Soares, Fernando A.; Linde, Sandra Aparecida Drigo [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Rogatto, Silvia Regina [UNESP] (Oxford University Press, 2012)
Endometriosis is a multifactorial gynecological disease characterized by the presence of functional endometrium-like tissue in ectopic sites. Several studies have focused on elucidating the immunological, endocrine, environmental and genetic factors involved in endometriosis. However, its pathogenesis is still unclear.High-resolution comparative genomic hybridization was applied to screen for genomic imbalances in laser microdissected stromal and epithelial cells from 20 endometriotic lesions and three samples of eutopic endometrium derived from eight patients. The expression of seven stemness-related markers (CD9, CD13, CD24, CD34, CD133, CD117/c-Kit and Oct-4) in endometrial tissue samples was evaluated by immunohistochemistry.Samples of eutopic endometrium showed normal genomic profiles. In ectopic tissues, an average of 68 genomic imbalances was detected per sample. DNA losses were more frequently detected and involved mainly 3p, 5q, 7p, 9p, 11q, 16q, 18q and 19q. Many of the genomic imbalances detected were common to endometriotic stroma and epithelia and also among different endometriotic sites from the same patient. These findings suggested a clonal origin of the endometriotic cells and the putative involvement of stem cells. Positive immunostaining for CD9, CD34, c-Kit and Oct-4 markers was detected in isolated epithelial and/or stromal cells in eutopic and ectopic endometrium in the majority of cases.The presence of shared genomic alterations in stromal and epithelial cells from different anatomical sites of the same patient and the expression of stemness-related markers suggested that endometriosis arises as a clonal proliferation with the putative involvement of stem cells.
Keywords: endometriosis; high-resolution comparative genomic hybridization; chromosomal imbalances; protein expression; stem cells